Overview of Poultry Eimeria Life Cycle and Host-Parasite Interactions - López-Osorio, Sara; Chaparro-Gutiérrez, Jenny J.; Gómez-Osorio, Luis M. (Frontiers in Veterinary Science, 2020)
Apicomplexan parasites of the genus Eimeria are organisms which invade the intestinal tract, causing coccidiosis, an enteric disease of major economic importance worldwide. The disease causes high morbidity ranging from an acute, bloody enteritis with high mortality, to subclinical disease. However, the presence of intestinal lesions depends on the Eimeria species. The most important poultry Eimeria species are: E. tenella, E. necatrix, E. acervulina, E. maxima, E. brunetti, E. mitis, and E. praecox. Key points to better understanding the behavior of this species are the host-parasite interactions and its life cycle. The present paper reviews the literature available regarding the life cycle and the initial host-parasite interaction. More studies are needed to better understand these interactions in poultry Eimerias, taking into account that almost all the information available was generated from other apicomplexan parasites that generate human disease.